Drogi szkolne młodzieży miejskiej i wiejskiej - uwarunkowania i konsekwencje = School paths of rural and urban youth - conditioning and consequences - Domalewski, Jarosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author considers the problem of differences in school paths in relation to environments. His analysis of changes in secondary and tertiary education after 1990 in Poland clearly shows the spreading of this level of education. As a consequence, the chances for continuing education in not easily available secondary schools have increased.
Keywords: szkolnictwo polskie; młodzież wiejska; młodzież miejska